2022
DOI: 10.1051/matecconf/202237207002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Needs Green Open Space Use Unmanned Aerial Vehicle (UAV) at Campus Area Of Musamus University Merauke

Abstract: Global warming due to the Greenhouse Gas Effect (GHG) occurs due to various sectors including agriculture, forestry, and industry. The forestry sector is the largest contributor to emissions reaching 43.92% in 2013. Musamus University (Unmus) is a state university located in the southern part of Papua, precisely in Merauke Regency. Unmus is a place for students to get education where the need for infrastructure is very necessaryamong themGreen Open Space (GOS) and Public Space. The development of the campus ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Infrastructure development in Southern Papua includes the expansion of Musamus University, a state university located in Merauke Regency. The campus area has expanded, with an increasing number of facilities and infrastructure being built, covering an area of ± 24,291 hectares by 2022 [1]. However, there is little information available on other specific infrastructure projects in Southern Papua.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Infrastructure development in Southern Papua includes the expansion of Musamus University, a state university located in Merauke Regency. The campus area has expanded, with an increasing number of facilities and infrastructure being built, covering an area of ± 24,291 hectares by 2022 [1]. However, there is little information available on other specific infrastructure projects in Southern Papua.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is little information available on other specific infrastructure projects in Southern Papua. In Papua Province, a study found that physical infrastructure development, such as electricity and roads, has a significant effect on poverty levels [1]. Another study conducted in Papua New Guinea, specifically on the Highlands Highway, assessed the impact of social and cultural factors on the implementation of highway projects [2].…”
Section: Introductionmentioning
confidence: 99%